Análisis del nivel de rentabilidad en las ventas de la empresa Altec S.A. durante el periodo 2019- 2020 - Mayorga Herrera, Tatiana Vanesa (2021)
This research has made it possible to carry out an analysis regarding the levels of profitability of the sales that the company Altec SA has in the city of Babahoyo, through the line of financial, administrative, tax, audit and control management in addition to the use of methods of analytical, descriptive and bibliographic research that have contributed to the achievement of the proposed objective and allowed to collect the necessary information through the application of the interview technique carried out with the head of the financial department of the company, in addition to an analysis of the financial statements provided that make it possible to show the causes and analyze the existing effects and their comparison with the established processes in scientific ways according to the criteria of various authors who support the research and have made it possible to determine facts such as: lacks the structuring of a detailed sales plan , a comparative analysis of Sales Figures are Frequent, Productivity Measurements are Not Made, Limited Actions are Executed for the Development of New Products, none of the United Nations Establishes SWOT Analysis The Same That Have an Impact on the Analysis That is Performed to Measure Profitability and Generate detailed reports applying the financial ratios that determine the reality of the company.